A Single Fluorescent Probe to Visualize Hydrogen Sulfide and Hydrogen Polysulfides with Different Fluorescence Signals. (13th July 2016) - Chen, Wei; Pacheco, Armando; Takano, Yoko; Day, Jacob J.; Hanaoka, Kenjiro; Xian, Ming
Abstract: Hydrogen sulfide (H2 S) and hydrogen polysulfides (H2 S n, n >1) are endogenous regulators of many physiological processes. In order to better understand the symbiotic relationship and cellular cross‐talk between H2 S and H2 S n, it is highly desirable to develop single fluorescent probes which enable dual‐channel discrimination between H2 S and H2 S n . Herein, we report the rational design, synthesis, and evaluation of the first dual‐detection fluorescent probeDDP‐1 that can visualize H2 S and H2 S n with different fluorescence signals. The probe showed high selectivity and sensitivity to H2 S and H2 Sn in aqueous media and in cells.